Survey Pemanfaatan Teknologi Informasi Dalam Pembelajaran Mahasiswa Keperawatan - Kartika, Imelda Rahmayunia (REAL in Nursing Journal, 2020)
Backgroud: Information technology has become a key choice in creating a robust organizational information system that is able to produce a competitive advantage amid increasingly stringent competition today. This research aims to determine the perception of respondents which in this case is nursing students about the utilization of information technology in the study of the courses of nursing management information System. Methods: The design of this research is descriptive analytic. The population in this study is odd semester students who take the course of nursing information System, which is as much as 90 people. Sampling using the total sampling technique. Data collection using questionnaires containing student perceptions about the tenology-based learning of information with Google forms. Results: The results showed that students were pleased with the utilization of information technology in learning. The most high student perception is about utilizing Google form in creating a questionnaire with mean 3.189 (SD = 0,598). In addition, a negative statement that has the lowest mean that states that information technology (IT) is difficult with mean 2.900 (SD = 0,704). In addition, 81% of respondents were interested in using IT on learning. IT can be concluded that respondents are not experiencing difficulties in using IT and are pleased with IT utilization in learning. Therefore, it is expected to all nursing lecturers to be able to use information technology in the learning in order to support the 4.0 Industrial Revolution Keywords: Technology, information, learning, nursing